Konsultasi Publik Kegiatan Pengembangan Rumah Sakit - Nita Marikena; Yuli Setiawannie; Susilawati, Susilawati (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
MM Hospital is one of the General Hospitals located on Jalan Sisingamangaraja, Harjosari I Village, Medan Amplas District, Medan City, North Sumatra Province. This hospital plans to develop its services in the health sector. Referring to Law No. 32 of 2009 concerning Environmental Protection and Management, Law No. 11 of 2020 concerning Job Creation, Government Regulation No. 22 of 2021 concerning the Implementation of Environmental Protection and Management and Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No. 4 of 2021 concerning List of Businesses and/or Activities Required to Have an Environmental Impact Analysis, Environmental Management Efforts and Environmental Monitoring Efforts or a Statement of Undertaking to Manage and Monitor the Environment Appendix I Letter F Health Sector No.12. and Annex II Letter A Multisector with criteria required to have AMDAL, UKL-UPL and SPPL, for building area ≥10,000 m2, AMDAL is required. So that development activities in health services by MM General Hospital, are required to prepare an Environmental Impact Analysis Document (AMDAL) Category C. Based on the results of the public consultation conducted on May 19, 2023, several important issues that became input in public consultation activities, among others, were grouped into the impact of increased vibration, the impact of liquid waste generation, the impact of increased employment and business opportunities, the impact of changes in community income and the impact of changes in community attitudes and perceptions.